Luminescent properties of Eu(ttfa)(3) complexes incorporated into MSU-4 mesoporous silica matrices - Saliba, Lucas Falquetti; Sousa Filho, Paulo Cesar de; Castro, Gustavo Rocha de [UNESP]; Serra, Osvaldo Antonio; Utrera Martines, Marco Antonio (Biointerface Research Applied Chemistry, 2016)
A luminescent material has been prepared through formation of the Eu3+ beta-diketonate complex [Eu(ttfa)(3)(H2O)(2)] in methanolic medium within the channels of MSU-4 ordered mesoporous silica by post-grafting synthesis. Using simple wet incorporation methods, the Eu3+ ions were first impregnated into the solids, which was followed by addition of the 2-thenoyltrifluoroacetonate (ttfa) ligand. For further comparison, an analogous sample of the functionalized silica was impregnated with the previously prepared [Eu(ttfa)(3)(H2O)(2)] complex. The materials were characterized by scanning and transmission electron microscopy (SEM/TEM), X-ray diffractometry (XRD), infrared spectroscopy (IR) and photoluminescence spectroscopy (PL). The photoluminescence studies at room temperature showed the characteristic absorption of the ligand in the ultraviolet range in the excitation spectra and remarkable differences were observed between the free and the immobilized complexes. The emission spectra displayed the typical Eu3+ intraconfigurational (4)f(6) lines, ascribed to transitions between the D-5(0) excited state and the ground multiplet (F-7(0-4)). Negligible emission from the organic part of the encapsulated species was detected, indicating that energy transfer from the ligand to the Eu3+ ion was quite efficient. Evaluation of the calculated radiative and non-radiative decay rates and comparison of the obtained Judd-Ofelt intensity parameters allowed for a strict correlation between the impregnation processes and the luminescence efficiencies of the prepared materials.
Keywords: mesoporous materials; lanthanide complex; photoluminescence